The association of spiritual/religious perfectionism with ego-strength and spiritual health - Mohammad Ali Besharat; morteza naghipour; Niloufar Farsijani (مجله علوم روانشناختی, 2021)
Background: Theory of spiritual/religious perfectionism (Besharat, 2017, 2018, 2019) has introduced this type of perfectionism as one of the determinants of spritual health. Aims: The present study has two main objectives: examining the relationship between spiritual/religious perfectionism and indices of spiritual health including religious well-being and existential well-being; and investigating the relationship between spiritual/religious perfectionism and ego-strength. Method: Method of the present descriptive study was correlational. Two hundred and forty seven volunteer students (115 males, 132 females) from the universities in Tehran participated in this study. All participants were asked to complete Spiritual/Religious Perfectionism Scale (SRPS), Spiritual Well-Being Scale (SWBS), and Ego-Strength Scale (ESS). Reults: The results revealed a significant positive association of spiritual/religious perfectionism with religious well-being, existantiel well-being, spiritual health, and ego-strength (p< 0.001). Conclusions: It can be concluded that spiritual/religious perfectionism is one of the determinants of spiritual and personality health. The findings also may support a new dimension of perfectionism, i.e. spiritual/religious perfectionism.